Learning about Programming and Epistemic Emotions: A Gendered Analysis (2020)
Programming courses often turn into courses with high percentage of desertion and, sometimes, result in a factor that drives students to abandon their careers, even when they are subjects highly relevant in the training of engineers in the areas of computer science, IT, and related careers. These courses demand high cognitive processes, which generate several emotions learning-related that, when taken into account and evaluated, could be used in favor of learning. Programming courses generate negative emotions in female students in a higher proportion than men, which may even lead them to abandon the career, widening the gender gap. In recent years, there has been a growing interest in the role of emotions in academic environments at university level, as well as for knowing the reason for the low participation of women, despite the importance of their role and skills, in computing areas. However, the interest in analyzing the emotions that emerge from students as they learn to program is quite recent. There is not an important number of studies around the emotions of women while they learn to program. The objective of this study is to analyze the behavior -at an emotional level- of students towards different teaching activities, establishing gender level comparisons, and considering the incorporation of elements of collaboration and gamification to identify differences in the emotions originated by these activities.